Coins of Shah Jahan : Creations of an Architect - Liddle, Andrew V., (Brill | Manohar Publishers & Distributors, 2017)
This book is a follow up to the author's Coinage of Akbar: The Connoisseur's Choice (2005), and Coins of Jahangir: Creations of a Numismatist (2013). Shah Jahan's currency is unique in several ways. His coins were issued before he ascended the throne, and continued to be issued till well after he was deposed and imprisoned by Aurangzeb, in AH 1068, even from Akbarabad and Shahjahanabad. A rupee issued from Junagarh as late as AH 1071 is available. The exquisite calligraphy appears in all the four contemporary styles, Nastaliq, Naskh, Sulus and Tughra which were in use. There is a fair sprinkling of couplets on the coins too. Nazrana coins were struck as usual. Nisars were issued in as many as four varieties in gold and at least forty-four in silver, including the pre-accession ones from Lahore and Kabul. Another special feature of coins minted by Shah Jahan is the many different ways in which the Emperor's name and titles appear on them. This comprehensive monograph illustrates over 850 specimens of Shah Jahan's coins from all over the world - from museums, auction catalogues and private collections. An effort has been made to update the study with images of coins surfacing lately with the addition of an appendix. Earlier classification of less common coins as "S" for scarce, "R" for rare, "RR" for rarer still and "RRR" for extremely rare has been retained for this work also. A specially written article on Nazrana Coins, by Arvind Chandra, and pictures of a rare set of dies of Shah Jahan's coins from the unique collection of Maj. (Dr.) M.K. Gupta - both extremely knowledgeable and eminent Mughal numismatists, add greatly to the value of this volume.